The Relationship Between Impulsivity and Suicidal Risk of University Student’s : The Moderating Effects of Empathy Ability - et. al., Choonkyung Kim, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The purpose of this study are to examine the moderating effect of empathy ability as moderator variable in order to know how much university student’s difficulties in impulsivity would influence on suicidal risk. To this end, a study was conducted on 772 students attending universities located in Daegu andGyeongbuk. For the research analysis, the three-step control regression analysis proposed by Baron and Kenny(1986) was used. The research results are as follows. First, analysis showed that themoderating effect of empathy abilityin the relationship between impulsivity and suicidal risk is significant. The higher the empathy ability, the lower the impact of impulsivity on suicidal risk.Second, Empathy ability was shown to control the impact of impulsivity on the suicidal risk sub-factor. The details are as follows. Empathy ability was found to moderated the influence of impulsivity on negative self-assessment, suicidal ideation, and hopelessness. The higher the empathy ability, the lower the impact of impulsivity on negative self-assessment, suicidal ideation, and hopelessness. In conclusion, this study confirm the important role of empathy ability to reduce suicidal risk and provide basic data for counseling and psychotherapy.